2018
DOI: 10.1007/s13361-018-1897-y
|View full text |Cite|
|
Sign up to set email alerts
|

Top Down Tandem Mass Spectrometric Analysis of a Chemically Modified Rough-Type Lipopolysaccharide Vaccine Candidate

Abstract: Recent advances in lipopolysaccharide (LPS) biology have led to its use in drug discovery pipelines, including vaccine and vaccine adjuvant discovery. Desirable characteristics for LPS vaccine candidates include both the ability to produce a specific antibody titer in patients and a minimal host inflammatory response directed by the innate immune system. However, in-depth chemical characterization of most LPS extracts has not been performed; hence, biological activities of these extracts are unpredictable. Add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…Additionally, decomposition has the potential to remove biologically relevant labile modifications . Of the studies that have investigated intact LOS or LPS, most directly analyze complex mixtures in a shotgun-type approach without separation. The shotgun mode can lead to signal suppression as well as generation of tandem mass spectra that are challenging to interpret owing to coisolation of isobaric and isomeric species (the chimera spectra problem). Only a few studies have reported online electrophoretic or chromatographic separations of intact LOS and LPS. ,, From these past reports, CE separations resulted in reduced sensitivity and peak broadening owing to the deleterious mixing of the makeup liquid with background electrolyte, and LC separations suffered from subpar efficiency for intact lipids …”
mentioning
confidence: 99%
“…Additionally, decomposition has the potential to remove biologically relevant labile modifications . Of the studies that have investigated intact LOS or LPS, most directly analyze complex mixtures in a shotgun-type approach without separation. The shotgun mode can lead to signal suppression as well as generation of tandem mass spectra that are challenging to interpret owing to coisolation of isobaric and isomeric species (the chimera spectra problem). Only a few studies have reported online electrophoretic or chromatographic separations of intact LOS and LPS. ,, From these past reports, CE separations resulted in reduced sensitivity and peak broadening owing to the deleterious mixing of the makeup liquid with background electrolyte, and LC separations suffered from subpar efficiency for intact lipids …”
mentioning
confidence: 99%
“…It is possible that interrupting synthesis of UDP‐GalNAcA induces a compensatory mechanism by which other UDP‐linked glycans are produced and incorporated into the LOS instead of UDP‐GalNAcA. With the recent development of top down tandem mass spectrometric analysis of intact LOS (Oyler et al , ; Klein et al , ), it would be interesting to compare the LOS composition between the a/e2 mutant and the WT strain. Similarly, it is possible that the mutant strain is encountering an accumulation of UDP‐linked glycans at its inner membrane cytoplasmic face, which could eventually affect the integrity of the cell envelope.…”
Section: Discussionmentioning
confidence: 99%
“…Lipidomics is the large-scale global study of pathways and networks of cellular lipids collectively termed as the “lipidome” and elucidation of the biochemical mechanism(s) underlying specific changes in lipid metabolism, for example, in response to infection or endotoxin treatment. In contrast, a single host or bacterial lipid can also be characterized for structural inference using MS . In contrast to fairly standardized genomics or proteomics, the high degree of molecular heterogeneity in lipids makes it analytically challenging to achieve a large-scale lipidomic analysis.…”
Section: Lipidomics Approachesmentioning
confidence: 99%